APLIKASI REGRESI KUANTIL PADA KASUS DBD DI KOTA PALU SULAWESI TENGAH - Idris, N; Rais, Rais; Utami, I T (JURNAL ILMIAH MATEMATIKA DAN TERAPAN, 2018)
Palu city is one of the cities with unstable changes of natural conditions. The natural conditions such as the frequency of rainy day, temperature and humidity which are always changeable bring bad impacts and will cause of diseases especially dengue hemorrhagic fever (DBD). Therefore, it needs an action to recognise whether or not the natural condition factor influences the spread of DBD and determines what factors of the natural condition can influence the spread of DBD. This research applied quantile regression in the case of DBD in Palu city. Quantile regression is an analysis technique regarding to the functional relationship between one dependent variable with one or more independent variables which can provide accurate and stable results even though there will be outliers. Based on the result of the research, it is obtained that the natural condition factor affected the spread of DBD. This is because from 3 natural conditions only 11 significant or influential quantiles on the tested data, the quantiles are 0,30; 0,35; 0,40; 0,45; 0,50; 0,55; 0,60; 0,65; 0,70; 0,75 and 0,80. Meanwhile the most influential factor of natural conditions in spreading DBD isÂ  the frequency of rainy day because it has positive which means that 1 progress of percentage will increase the quantity of DBD case.